EFFECT OF COUNSELLING GUIDANCE IN IMPROVING PROCESS OF STUDENT LEARNING ACHIEVEMENT IN MTS NEGERI I BOJONEGORO - Asrori Asrori (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Muhammadiyah Gresik, 2019)
Quality education is one that integrates several fields of activity in synergy namely administrative, instructional and guidance and counselling. This research aimed to transform the knowledge into the education system integrally. The type of research used is field research (field resources) with a quantitative approach. In this research, there were two variables, namely Guidance and Counselling as independent variables, and student achievement as a dependent variable. The researcher conducted a study in MTs Negeri I Bojonegoro and the researchers selected grade 7 students as population, and assigned 10% of them as samples. Techniques in sampling in the form of random sampling. The source of this research data obtained by the method of observation, interview, questionnaire and documentation. The results of this research showed that counselling and guidance services affect the process of improving student achievement. This is based on the questionnaire score data that has been calculated with the product moment formula that results in a correlation index value (rxy) of 0.681. This result proved larger than the value at the significance level of 5% of 0.361 and 1% of 0.463. The results of this study indicate that there is influence between Counselling Guidance on the process of improving student achievement in MTs Negeri I Bojonegoro.